Hands-On Simulation Modeling with Python : Develop simulation models for improved efficiency and precision in the decision-making process - Ciaburro, Giuseppe (Packt Publishing Ltd., 2022)
Simulation modelling is an exploration method that aims to imitate physical systems in a virtual environment and retrieve useful statistical inferences from it. The ability to analyze the model as it runs sets simulation modelling apart from other methods used in conventional analyses. This book is your comprehensive and hands-on guide to understanding various computational statistical simulations using Python